2022
DOI: 10.1002/jlb.5mr0722-777r
|View full text |Cite
|
Sign up to set email alerts
|

γδ T cell exhaustion: Opportunities for intervention

Abstract: T lymphocytes are the key protective contributors in chronic infection and tumor, but experience exhaustion by persistent antigen stimulation. As an unconventional lineage of T cells, γδ T cells can rapidly response to varied infectious and tumor challenges in a non-MHC-restricted manner and play key roles in immune surveillance via pleiotropic effector functions, showing promising as candidates for cellular tumor immunotherapy. Activated γδ T cells can also acquire exhaustion signature with elevated expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…gd T cells are equipped with a T-cell Receptor (TCR) composed of a g-chain (TRG) and a d-chain (TRD). The genes encoding TRG and TRD undergo somatic DNA recombination of variable (V), diversity (D, only in TRD) and joining (J) elements during gd T cell maturation in the thymus (1). gd TCR and ab TCR are structurally similar and associated with the same subunits of the CD3 complex which, however, are arranged differently and characterized by unique glycosylation patterns and other minor peculiarities (2, 3).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…gd T cells are equipped with a T-cell Receptor (TCR) composed of a g-chain (TRG) and a d-chain (TRD). The genes encoding TRG and TRD undergo somatic DNA recombination of variable (V), diversity (D, only in TRD) and joining (J) elements during gd T cell maturation in the thymus (1). gd TCR and ab TCR are structurally similar and associated with the same subunits of the CD3 complex which, however, are arranged differently and characterized by unique glycosylation patterns and other minor peculiarities (2, 3).…”
Section: Introductionmentioning
confidence: 99%
“…The genes encoding TRG and TRD undergo somatic DNA recombination of variable (V), diversity (D, only in TRD) and joining (J) elements during γδ T cell maturation in the thymus ( 1 ). γδ TCR and αβ TCR are structurally similar and associated with the same subunits of the CD3 complex which, however, are arranged differently and characterized by unique glycosylation patterns and other minor peculiarities ( 2 , 3 ). One major difference are the antigens recognized by αβ and γδ T cells and the modality of antigen recognition which is not dependent on the major histocompatibility complex (MHC) in γδ T cells ( 2 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The predominant T cell type in the body is ab T cells (here referred to simply as T cells), and these express ab TCRs consisting of an aand a b subunit, while gd T cells express TCRs consisting of a gand a d subunit (21). Studies provides insights in the acquirement of an exhaustion signature by gd T cell, which has been extensively reviewed by Chen et al (22). Furthermore, it has been reported that gd T cells can have immunosuppressive functions, imposing immune exhaustion of antitumor ab T cells through PD-1/PD-L1 signaling (23).…”
Section: Introduction 1t Cell Exhaustionmentioning
confidence: 99%